The Effect of Symptoms on the Survival Time of Coronavirus Patients in the Sudanese Population - Shokeralla, Alshaikh A.; Qurashi, Mohammedelameen E.; Mekki, Reem Yousif; Ali, Mortada S. (International Journal of Statistics in Medical Research, 2023)
The COVID-19 pandemic has rapidly spread worldwide, resulting in substantial rates of illness and death. Gaining insight into the various factors that impact the duration of survival among individuals diagnosed with COVID-19 is of utmost importance to inform clinical practices and public health strategies This study aims to evaluate the relationship between the acuteness of symptoms and the survival time of coronavirus patients in Sudan. The Kaplan-Meier curves and log-rank test were used to determine the symptom pattern. The results of COVID-19 and Cox regression were utilized to determine the most critical symptoms affecting coronavirus patients. The log-rank test revealed that there are differences in the pattern of age and symptoms among coronavirus patients. Cox regression revealed that symptoms affect on the survival time of coronavirus patients. The Cox proportional Hazard Model shows that the hazard of age at any time increases by 116.5%, diarrhea increases by 9%, headache increases by 62.0%, fatigability increases by 13.3%, and other symptoms increase by 47.3%. This study differs from prior studies in several ways. No current study in Sudan has used survival analysis to discover the most relevant symptoms affecting survival time.